CFD‐based simulation study on producer gas explosion in an electrostatic precipitation. Issue 1 (27th April 2015) - Yang, Kai; Li, Qiang; Ding, Zhijiang; Xiao, Lichun
Abstract : Gas explosion is one of the most serious problems in the operation of electrostatic precipitation (ESP) which is applied to purify producer gas. Simulation study on the producer gas explosion in ESP has been conducted with computational fluid dynamic method. Producer gas explosion was studied experimentally in a closed rectangular vessel to validate simulation results. Numerical results were proved to be reliable and reasonable which could meet the engineering needs. The factors of flame propagation and pressure variation have also been analyzed. Furthermore, the effects of those explosion parameters such as premixed oxygen concentration, operating conditions, and local gas clouds with high oxygen content were discussed. The results show that maximum explosion pressure rises sharply with the premixed oxygen concentration increasing. Meanwhile, maximum explosion pressure increases with the operating pressure boosting, but decreases while the operating temperature elevates. Explosion pressure of local gas cloud with high oxygen content is a linear function of its volume. For this model, the critical diameter of gas clouds is 1.2 m with the oxygen concentration of 20%. The volumetric ratio of gas clouds in this model is 0.04. This study gives a reference for the optimization of oxygen monitoring‐feedback system response, and can provide theoretical guidance for the design of explosion protection. © 2015 American Institute of Chemical Engineers Process Saf Prog 35: 96–102, 2016